KAJIAN YURIDIS UNTUK EKSEKUSI HAK TANGGUNGAN ATAS KREDIT PERSEROAN TERBATAS DENGAN AGUNAN ASET PRIBADI (Studi kasus Putusan atas Perkara Nomor 348/Pdt.G/2020/PN Sby) - Linda Sholihatin; Ibnu Arly (Jurnal Hukum dan Bisnis (Selisik), 2022)
To carry out economic activities, the existence of capital is very necessary because it is used to finance these activities and capital in this case can be in the form of assets or money. It’s just that related to physical activities, money is the most important capital. To obtain this capital, apart from personal funds, it can also be obtained from third parties in the form of investment, issuance of shares or loan funds. Judging from the level of ease of obtaining capital funds, loan funds are the easiest compared to others and only involve a few parties so that business people prefer to borrow to obtain the capital. One of the parties providing loans in accordance with the legislation is bank and non-bank financial institutions, where to obtain the loan the debtor must make a credit agreement first and the debtor has an obligation to repay the loan plus a certain margin commonly known as interest. Banks and non-bank financial institutions have the principle of prudence in carrying out their functions so that for this purpose they apply the 5C requirements in providing credit, namely: (a) character (debtor character); (b) capacity (debtor’s ability to receive and repay loans); (c) capital (financial capital owned by the debtor); (d) collateral (collateral provided); and (e) condition of economic (economic condition for debt repayment risk). One of the most important is about guarantees where just in case the debtor cannot repay the loan, there are various kinds of guarantees in providing credit, one of which is a personal guarantee where parties outside the debtor and creditor 93are willing to give their assets to be used as collateral in the credit agreement. debtor. Based on the Civil Code, the guarantee provided by a third party (the guarantor) has the same rights as the guarantee provided by the debtor, so that if the debtor defaults, the guarantee provided by the insurer has the right to be executed by the creditor because the nature of the guarantee is to surrender voluntarily to someone else. Even though it seems detrimental to the insurer if the debtor defaults, the law has guaranteed the safety of collateral belonging to third parties from the debtor and creditor game, namely providing conditions that must include SKMHT and APHT in providing guarantees so that if there are none, the creditor cannot execute the goods belonging to the insurer